What Constitutes a Clinically Important Pain Reduction in Patients after Third Molar Surgery? - Wilhelmus JJM Martin; CE Ashton-James; NE Skorpil; MW Heymans; T Forouzanfar (Pain Research and Management)
BACKGROUND: For patients with surgical third molar removal, it is unknown what constitutes a clinically important change in patients’ visual analogue scale (VAS) reports of pain intensity.